1982
DOI: 10.1029/jb087ib05p03755
|View full text |Cite
|
Sign up to set email alerts
|

Paleomagnetism of small basalt exposures in the West Puget Sound Area, Washington, and Speculations on the accretionary origin of the Olympic Mountains

Abstract: Twenty‐two sites from two small exposures of basalt of probable Eocene age immediately east of the Olympic Mountains have the following mean paleomagnetic direction: declination, 176.5°; inclination, −66.5°; circle of 95% confidence, 8.6°. This is the only paleomagnetic study of pre‐Miocene rocks anywhere in western Washington or Oregon that matches the polar wandering curve for North America. However, a marked fanning of paleomagnetic declinations around the Olympic core suggests that concordance in this case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Folding of the Olympic structure into its present broad horseshoe shape ( Fig. 1) may have occurred during accretion (Tabor and Cady 1978b;Beck and Engebretson 1982) or during more recent extension in the Pacific Northwest.…”
Section: Tectonic Styles Compressional Tectonicsmentioning
confidence: 97%
“…Folding of the Olympic structure into its present broad horseshoe shape ( Fig. 1) may have occurred during accretion (Tabor and Cady 1978b;Beck and Engebretson 1982) or during more recent extension in the Pacific Northwest.…”
Section: Tectonic Styles Compressional Tectonicsmentioning
confidence: 97%
“…Whether these basalts were formed on an oceanic plate and were accreted to North America, or are the result of a rift within the western margin of North America has been controversial [Wells et al, 1984;Babcock et al, 1992]. Rotations of the Coast Range basalts increase from none at the north [Beck and Engebretson, 1982;Irving and Massey, 1990; this paper] to as much as 80 ø of net clockwise rotation to the south [Simpson and Cox, 1977;Wells et al, 1985;Beck, 1989b;Wells, 1990] (Figure 1). Wells and Heller [1988] addressed the relative contribution of three proposed rotation mechanisms: rotation during accretion [Simpson and Cox, 1977;Magill et al, 1981;Duncan, 1982], nonrigid dextral shear rotation due to coupling between North America and the obliquely converging Farallon or Kula plates [Beck, 1976[Beck, , 1980Reidel et al, 1984;Sheriff, 1984], and rigid rotation due to differential extension of the Basin and Range Province [Simpson and Cox, 1977;Magill et al, 1981;Frei et al, 1984;Groinrod et al, 1986].…”
Section: Introductionmentioning
confidence: 99%
“…Wells and Heller [1988] concluded that a combination of rotations due to Basin and Range extension and oblique convergence fits the geologic and palcomagnetic data without invoking complicated accretion models. The lack of rotation found in the northern Coast Recent palcomagnetic studies of the upper (subaerial) portion of the Crescent Formation in and near the Olympic Mountains (Figure 2) [Beck and Engebretson, 1982;Purdy, 1987;Warnock, 1989] found apparent rotations, but lacked the broad geographic coverage required to unravel the regional structural and tectonic history. Magnetizations from intrusive rocks of the correlative Metchosin Igneous Complex on southern Vancouver Island (Figure 2) are concordant, but lack local structural control [Irving and Massey, 1990].…”
Section: Introductionmentioning
confidence: 99%
“…results, and the data from the Crescent Formation to the south, all other rocks on the north flank of the Olympic Peninsula show a counterclockwise rotation. Beck and Engebretson [66] reported no net rotation of the Eocene Bremerton volcanic rocks, east of the Olympic Mountains. All paleomagnetic data south and southeast of the Olympic Mountains, including the Blakely Formation, the Humptulips Formation, and many earlier results on Eocene rocks south of the Olympics [67][68][69][70][71][72][73] show a consistent clockwise rotation.…”
Section: Tectonic Rotationmentioning
confidence: 99%